2/5g-1/3=-10/3

Simple and best practice solution for 2/5g-1/3=-10/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2/5g-1/3=-10/3 equation:


g in (-oo:+oo)

(2/5)*g-(1/3) = -10/3 // + -10/3

(2/5)*g-(1/3)-(-10/3) = 0

(2/5)*g-1/3+10/3 = 0

2/5*g+3 = 0 // - 3

2/5*g = -3 // : 2/5

g = -3/2/5

g = -15/2

g = -15/2

See similar equations:

| 4x+11=195 | | 3x+17=x+53 | | (x-12)/(3-x)=(x+33)/(x+3) | | (x^4)+(-10x^2)+(9)=0 | | x+3x+17=109 | | 20c=398 | | 8x-9=4x-7 | | 398c=20 | | 100=-5x | | 4x+2y=-3 | | 2x+65=6x+9 | | 3x-24=x+4 | | -7.3-5.18=-51.9 | | 4(4w+5)+3w=8(w+7)-3 | | 3x^3-51x=0 | | 20c=183 | | 22=2(4a+2) | | 20c=89 | | 5x+3-2x+11=x-6+x+14 | | 183w=4 | | -3x+1=-26 | | x^4-6x^2=-4 | | 4c=89 | | -3(7-2y)=-14-1 | | .05x+10(200-x)=.45x | | (x^4)+(-10x^2)+(16)=0 | | 2(y-3)=4x | | -1(8m+4)=4m-2(6m+2) | | -2x+7=2 | | (x^4)-(12x^2)+(11)=0 | | 0.5y+1=4x-2 | | 2x-5y=28 |

Equations solver categories